(untitled) (REVISTA NODO, 2012)
The article is the product of a research/creation dealing with the relation between art and violence in Colombia. It begins by giving a brief description of three well-delimited violent periods according to outstanding historians, and by closely analyzing the Massacre of Trujillo as understood by Historical Memory, a group part of the National Reparation and Reconciliation Commission. Then, the author provides a breviary of the most prominent Colombian artworks in relation to violence, and proposes a meditation around the standpoint that artists should take towards this particular issue. Subsequently, it presents some art proposals originated by the Massacre of Trujillo, as well as artworks inspired on Colombian rivers for being places where tragedy and truncated mourning rituals converge. Finally, the article introduces Río, the product of the research process, an artwork articulating the landscape and the unmonumental as categories for creative exploration.